Smart bioimpedance-controlled craniotomy: Concept and first experiments. (July 2017) - Niesche, Annegret; Müller, Meiko; Ehreiser, Fritz; Teichmann, Daniel; Leonhardt, Steffen; Radermacher, Klaus
Craniotomy is part of many neurosurgical interventions to create surgical access to intracranial structures. The procedure conventionally bears a high risk of unintended dural tears or damage of the soft tissue underneath the bone. A new synergistically controlled instrument has recently been introduced to address this problem by combining a soft tissue preserving saw with an automatic cutting depth control. Many approaches are known to obtain the information required on the local bone thickness. However, they suffer from unsatisfactory robustness against disturbances occurring during surgery and many approaches require additional intra- or preoperative steps in the workflow. This article presents first concepts for real-time cutting depth control based on in-process bioimpedance measurements. Furthermore, sensor integration into a synergistic surgical device incorporating a bidirectional oscillating saw is demonstrated and evaluated in first feasibility tests on a fresh bovine bone specimen. Results of bipolar measurements show that the transition of different layers of bicortical bone and bone breakthrough lead to characteristic impedance patterns that can be used for process control.